Economic reforms : role of states and the future of centre - state relations - "Gupta, Parul (ed.)" (New Delhi, 1996)
The arena of fiscal federalism in India, which had been a minefield of political conflicts even in the Pre-reform era, has been showing signs of becoming a full-fledged battlefield in the wake of the economic reform Programme initiated in 1991. In March 1995, the observer Research Foundation sought to bring the various problems in Centre-state relations, which had surfaced in the wake of the reforms, to the forefront of the policymaker' agenda through a national seminar on ' Economic Reforms : the role of states and the future of Centre-state relations'.
Keywords: Centre state relations